1999
DOI: 10.1002/(sici)1099-1166(199912)14:12<1019::aid-gps61>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Decreased awareness of cognitive deficits in patients with mild dementia of the Alzheimer type

Abstract: Objective To study the unawareness of cognitive deficits in patients with mild dementia of Alzheimer type (DAT). Design Retrospective study. We surveyed the medical records of outpatients meeting the NINCDS–ADRDA criteria for probable DAT who were able to complete the Cognitive Difficulties Scale (CDS) and had a close informant relative (IR) who could complete the family form of the same questionnaire. Setting A department of neurology in a general teaching hospital. Subjects Eighty‐eight patients, aged 73.2±8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0
19

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(97 citation statements)
references
References 52 publications
8
70
0
19
Order By: Relevance
“…In addition, apathy can increase caregiver burden (Hart et al 2003;Kaufer et al 1998;Pang et al 2002;Thomas et al 2001). Apathy may also reduce quality of life of the patient (Samus et al 2005); although it has been suggested that apathy may not be a concern to the patient themselves and has been associated with lack of awareness in dementia (Aalten et al 2006;Derouesne et al 1999). …”
Section: Apathymentioning
confidence: 99%
“…In addition, apathy can increase caregiver burden (Hart et al 2003;Kaufer et al 1998;Pang et al 2002;Thomas et al 2001). Apathy may also reduce quality of life of the patient (Samus et al 2005); although it has been suggested that apathy may not be a concern to the patient themselves and has been associated with lack of awareness in dementia (Aalten et al 2006;Derouesne et al 1999). …”
Section: Apathymentioning
confidence: 99%
“…Selfrating of cognitive deficits is also proposed as an index of cognitive unawareness, because AD patients report cognitive impairment that they frequently do not find particularly abnormal for their age (Cummings et al, 1995). Loss of insight may be evaluated by the clinician, on the basis of patient answers to questions probing awareness of cognitive deficits (expert judgment), or by caregivers assessing the frequency of behavioral manifestations of unawareness in everyday life (Derouesne et al, 1999). While most patients with mild cognitive impairment (MCI) tend to overestimate their cognitive deficits when compared to their caregiver's assessment, AD patients in early stages of the disease with similar MMSE scores underestimate their cognitive dysfunction (Kalbe et al, 2005).…”
Section: Behavioral Measures Of Anosognosia In Admentioning
confidence: 99%
“…Studies relating anosognosia to brain activity have shown a decrease of right lateral frontal and parietal activity in AD patients with anosognosia (Leys et al, 1989;Starkstein et al, 1995;Derouesne et al, 1999). In a theoretical model, the ''conscious awareness system'' was suggested to depend on inferior parietal and posterior cingulate cortex (McGlynn and Schacter, 1989).…”
Section: Behavioral Measures Of Anosognosia In Admentioning
confidence: 99%
“…Este relato preliminar aponta para uma diferença significativa na consciência da doença entre os grupos CDR 1 e CDR 2, achado este que corrobora p e s q u i s a s 6,8,13,20 sobre o grau de consciência da d o e n ç a e a evolução clínica. Assim, a consciência da doença diminui na medida em que a doença progride.…”
Section: Discussionunclassified
“…Isto é consistente com o fato de os indivíduos estarem conscientes de determinadas perdas, mas não de outras, ou então, perceberem os déficits, mas não as suas conseqüências 6,20 . Um estudo 13 encontrou correlação positiva entre consciência da doença e idade, mais precisamente com o início tardio da doença. Em nosso estudo a correlação encontrada siderada parcialmente comprometida.…”
Section: Discussionunclassified